Analisis Faktor-Faktor Yang Mempengaruhi Minat Siswa Untuk Melanjutkan Pendidikan Ke Perguruan Tinggi - Swandewi, Ida Ayu Putu Manik; Wijana, I Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education is a process of changing the attitudes and behavior of a person or group of people in an effort to improve their identity through guidance in seeking knowledge where each person needs to go through a process in order to become the best in a life that can fulfill their needs. So, the process of seeking knowledge is very beneficial for the future so that you can go through a process that will be a challenge in your future life in order to have high competitive value. Education or upbringing is a planned basic effort to create an atmosphere of learning and learning so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, morals, life sciences, general knowledge and the skills they need for society based on the Law. Invite the learning of the knowledge, skills, and habits of a group of people that are passed from one generation to the next through teaching, training, or research.